Random aggregates in newly produced platelet units are associated with platelet activation and release of the immunomodulatory factors sCD40L and RANTES. Issue 3 (28th July 2013) - Sandgren, Per; Meinke, Stephan; Eckert, Elias; Douagi, Iyadh; Wikman, Agneta; Höglund, Petter
<x xml:space="preserve">Abstract</x> Background In connection with platelet (PLT) production, random but transient aggregates sometimes form in the newly produced units. The underlying mechanisms as well as the impact on cellular level of this phenomenon are unknown. Hypothetically, random occurrence of aggregates may induce biochemical changes leading to PLT activation and release of immunomodulatory factors from the PLTs. Study Design and Methods PLTs were aliquoted and prepared with an automated system for PLT pooling (OrbiSac, Terumo BCT) for a three‐arm nonpaired study design (n = 8). Initially aggregated PLT units in SSP+ were selected by visual inspection and compared to unaffected PLT units stored in SSP+ or 100% plasma. Cellular, metabolic, and functional variables were analyzed, including the concentrations of RANTES, sCD40L, and sTWEAK in the bags during a 9‐day storage period. Results Isolated aggregated PLTs show signs of spontaneous activation and respond less efficiently to TRAP stimulation. RANTES, sCD40L, and sTWEAK accumulated in the various PLT units during storage but sCD40L and RANTES accumulated in the initially aggregated PLT units to higher concentrations than the reference units and PLTs stored in 100% plasma (p < 0.001). Over time, the levels of sTWEAK increased more in the plasma storage environment compared with PLT units stored in SSP+ (p < 0.001). Conclusion Our data indicate that random occurrence of aggregates may lead to higher activation level and increased release of immunomodulatory factors from the PLTs.